Inhibition of human N myristoyltransferase 1 as a strategy to suppress cancer progression driven by myristoylation - Mohammed Merae Alshahrani (Scientific Reports)
Abstract N-myristoyltransferase 1 (NMT-1) catalyzes the co-translational addition of myristic acid to the N-terminal glycine of substrate proteins, regulating membrane localization and protein-protein interactions essential for oncogenic signaling. Its overexpression in diverse malignancies has rendered NMT-1 a valuable target for anticancer drug discovery. The study identified four promising inhibitors (Diverse-lib ID: 17506136, 103050917, 24289547, and 24314423) with docking scores ranging from − 11.5 to − 11.2 kcal/mol. DFT analysis revealed favorable frontier orbital characteristics, particularly in 24,289,547, which exhibited the lowest HOMO–LUMO ΔEgap (3.516 eV), supporting its electronic suitability for enzyme binding. Redocking of optimized ligands into the active site of NMT-1 confirmed key interactions with catalytic residues Asp184, Asp471, Phe188, Tyr296, and His298. 500-ns molecular dynamics (MD) simulations (in triplicate) demonstrated that compound 24,289,547 consistently retained stable binding, as evidenced by low root-mean-square deviation (RMSD) values, persistent hydrogen bond interactions, and tightly clustered conformations in principal component analysis (PCA). Free energy landscape analysis further highlighted 24,289,547 convergences into a single, deep thermodynamic basin. MM/GBSA binding energy calculations identified 24,289,547 as the most favorable inhibitor (ΔG_total = − 102.72 kcal/mol), exceeding the reference compound. Structural superposition with initially docked poses yielded RMSD < 1.25 Å, indicating conformational fidelity. Collectively, these findings establish 24,289,547 as a leading NMT-1 inhibitor candidate. Its stable interaction with the Asp184–Asp471 catalytic motif and peripheral residues suggests a robust biochemical basis for inhibition, offering significant promise for further optimization and therapeutic application in NMT-1-associated cancers.